Pengaruh Kualitas Produk,Kualitas Pelayanan Dan Media Sosial Terhadap Keputusan Pembelian ( Studi Pada UKM Makaroni Bantet Banyuwangi ) - Husnul Hotimah; Muhammad Firdaus; Saiful Amin (JMBI : Jurnal Manajemen Bisnis dan Informatika, 2022)
This study aims to determine the effect of product quality, service quality, and social media on purchasing decisions for macaroni bantet Banyuwangi. This study is based on quantitative methods, the data used in this study are primary data obtained from respondents' responses to questionnaires. Samples were taken as many as 100 respondents with a sampling technique using a simple random sample. The data obtained is then processed using SPSS analysis tools, analysis method using multiple linier regression analysis. The results showed that the variables of product quality, service quality, and social media had a simultaneous effect on purchasing decisions.